La reparación por vía administrativa a la comunidad Wayuu de Bahía portete en el marco de la ley 1448 de 2011 (2019)
Under Law 1448 of 2011 Law on Victims and Restitution of Lands- regulated by Decree 4633 of 2011, the extent of administrative reparation to the Wayuu community for the events of the Portete Bay massacre was discussed, having as points to be analyzed the worldview of the Wayuu community, the process of repair and the applicability which has been given to the guidelines established by the Law in the recognition as victims of indigenous communities and the regulations implemented for land repair and restitution purposes. In principle, the institutionality raised by the State for the implementation of the Victims Act, provided for the interaction of corporations in order to ensure their applicability, as compared to the principles of truth, justice, reparation and guarantee non-repetition, which allowed the wayuu worldview to be contrasted with the purpose of analyzing the problem raised.